Local labor markets should be redefined: New definitions based on estimated demand-shock spillovers - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2024)
This paper provides estimates that lead to better U.S. labor market definitions. Current U.S. labor market definitions-for example, metropolitan areas and commuting zones-are unsatisfactory because they are ad hoc and usually do not correspond to commonly used local planning areas. This paper proposes basing U.S. labor market definitions on how a job shock to a county affects nearby counties' employment rates. New estimates of county spillovers are presented. Using these estimated spillovers, new multicounty labor market definitions are based on maximizing a weighted sum of total spillovers captured, versus taking the average size of within-market effects. These new "spillover-defined local labor markets" (SLMs) correspond more closely to commonly used local planning areas, and they better capture spillovers and commuting flows without becoming excessively large.
Keywords: R10; R12; R23; 330; Local labor markets; commuting zones; metropolitan areas